2009
DOI: 10.1007/s12020-009-9212-0
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical performance of diaphyseal shafts and bone tissue of femurs from hypothyroid rats

Abstract: The bone changes in hypothyroidism are characterized by a low bone turnover with a reduced osteoid apposition and bone mineralization rate, and a decreased osteoclastic resorption in cortical bone. These changes could affect the mechanical performance of bone. The evaluation of such changes was the object of the present investigation. Hypothyroidism was induced in female rats aged 21 days through administration of propylthiouracil in the drinking water for 70 days (HT group). Controls were untreated rats (C gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
2
3
0
Order By: Relevance
“…Indeed, a number of clinical studies reported increased body weight gain in adult and children with hypothyroidism [ 14 , 31 ]. In contrast, most animal studies found decreased body weight both in adult [ 3 ] and immature [ 9 , 33 ] rats, in agreement with our results ( Fig. 1B ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Indeed, a number of clinical studies reported increased body weight gain in adult and children with hypothyroidism [ 14 , 31 ]. In contrast, most animal studies found decreased body weight both in adult [ 3 ] and immature [ 9 , 33 ] rats, in agreement with our results ( Fig. 1B ).…”
Section: Discussionsupporting
confidence: 93%
“…As expected, we found impaired long bone growth in RAI-treated immature rats ( Figs. 2 and 3 ) as consistent with previous reports [ 9 , 20 ]. On the other hand, BMC mainly increases during the pubertal growth spurt [ 12 ] and thyroid hormone has opposing effects on bone mineralization depending on bone maturational status [ 7 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The biomechanical properties of the right femur were assessed using a diaphysis bending test [ 18 ] on a WD-1 Universal Testing Apparatus (KeXin Testing Machine Co., Ltd., Changchun, China) that was equipped with calculation and analysis software. The two ends of the right femur were horizontally fixed on the three-point bending platform, and a vertical compression load was then applied to the mid-point of the femur at a displacement rate of 2 mm/min.…”
Section: Methodsmentioning
confidence: 99%
“…Hypothyroidism was implicated in the reduction of body temperature; in increase in sensitivity of receptors dopaminergic agonists to certain drugs like apomorphin, quinpyrole, and 3-benzopine; and in reduction of antagonistic receptors in other studies done in PTU treated young rats [ 63 ] . In addition, studies carried out by various researchers in rats showed that hypothyroidism provokes bone tissue changes characterized by rigidity in bone movement due to reduced osteoid and mineralization index of the bones, and osteoclastic absorption [ 64 ] . Other studies performed in mice with TTF-1 and PAX 8 defi ciencies, 2 transcriptional factors known to be essential for organogenesis with diff erential function in thyroid glands, gave the evidence of the mutagenic origin of CH by dysgenesis of thyroid gland [ 65 ] .…”
Section: Other Alterationsmentioning
confidence: 99%